2014
DOI: 10.1021/ac503102g
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Selective, and Ultrasensitive Fluorimetric Analysis of Mercury and Copper Levels in Blood Using Bimetallic Gold–Silver Nanoclusters with “Silver Effect”-Enhanced Red Fluorescence

Abstract: Bimetallic alloying gold-silver nanoclusters (Au-AgNCs) have been synthesized by a one-pot biomineralization synthesis route at a vital molar ratio of Au/Ag precursors in the protein matrix. Unexpectedly, the prepared Au-AgNCs could exhibit dramatically enhanced red fluorescence, which is about 6.5-fold and 4.7-fold higher than that of common AuNCs and core-shell Au@AgNCs, respectively. A rapid, selective, and ultrasensitive fluorimetric method has thereby been developed using Au-AgNCs as fluorescent probes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(116 citation statements)
references
References 36 publications
8
108
0
Order By: Relevance
“…1. Here, the test strips were first loaded with the model probes of fluorescent Au-AgNCs49 and then dried in vacuum on a lotus surface-like hydrophobic pattern, which was created by coating the Hexadecyltrimethoxysilane (HDS) on the glass slides. As expected, the uniform distribution of dispersed fluorescent probes on test strips would be realized upon the suppressed “coffee stains”.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Here, the test strips were first loaded with the model probes of fluorescent Au-AgNCs49 and then dried in vacuum on a lotus surface-like hydrophobic pattern, which was created by coating the Hexadecyltrimethoxysilane (HDS) on the glass slides. As expected, the uniform distribution of dispersed fluorescent probes on test strips would be realized upon the suppressed “coffee stains”.…”
Section: Resultsmentioning
confidence: 99%
“…Herein, the possible interference from Cu 2+ ions could be prevented by introducing the strong chelating agents of ethylenediaminetetraacetic acid (EDTA) with high enough concentration optimized as 5.0 μM, since the Cu 2+ -induced quenching mechanism might involve the interactions between Cu 2+ ions and the protein scaffolds of Au-AgNCs by producing the protein−Cu 2+ complex53. In contrast, the fluorescence of Au-AgNCs could be quenched by Hg 2+ ions through the formation of strong metallophilic Au−Hg 2+ bonding, of which the lost fluorescence might not be recovered by EDTA49. In addition, the common anions might present no significant effect on the sensing selectivity of the developed fluorimetric test strips, as shown in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some metal ion sensor-based Ag/Au bi metallic NCs are as follows. Zhang et al established the Au/Ag NCs in the protein matrix with "Silver Effect"-enhanced red fluorescence [174]. Importantly, the above-mentioned probe Au-Ag NCs facilitated the recognition of Hg 2+ and Cu 2+ ions with corresponding LODs of 0.30 and 0.60 nM in blood samples.…”
Section: Bi-metallic Nanoclusters In Sensors and Bio-imagingmentioning
confidence: 99%
“…Therefore, the doped-element of the alloy NCs is an important parameter for the optical properties of the bimetallic NCs. Compared with other proteins (e.g., lysozyme, trypsin, and pepsin) as stabilizing and reducing agent to synthesize NCs [19][20][21], BSA was used as a nontoxic agent to reduce Ni(II) and Au(III) ions, and also as a stabilizer for the NCs as described earlier for similar cases [14,16]. We carefully investigated the effects of doped-element on the FL intensities and the reaction between alloy NCs and the Cd 2+ or Hg 2+ ions, such as Nidoped and Pt-doped Au NCs.…”
Section: Choice Of Materialsmentioning
confidence: 99%
“…fluorescent nanoprobe, research in the detection heavy metal ions application of noble metal-doped Au NCs is still rare. Up to now, to the best of our knowledge, merely fluorescent approaches have been reported that can be used to detect different metal ions by fluorescent bimetallic NCs material or other sensing platforms [16].…”
Section: Introductionmentioning
confidence: 99%